One god, two goddesses, three studies of South Indian cosmology - Handelman, Don. (Jerusalem Studies in Religion and Culture, 2013)
One, God, Two Goddesses presents three studies, one of Tamil myths of the god Murugan and two of goddess rituals: Gangamma in Tirupati and Paiditalli in Vizianagaram, both in Andhra Pradesh. All three essays search for lineaments of the cosmos that these deities inhabit and shape. These cosmoi are characterised by the dynamism of their incessant interior movement. Should they become still, they would die. Deities activate and regenerate such a cosmos. The dynamism of Murugan's cosmos eliminates the chaotic. Through ritual, Gangamma regenerates her cosmos through feminising it. Through ritual, Paiditalli annually re-grows the historic little kingdom of Vizianagaram, regenerating its kingship. All three studies point to the need to rethink cosmology in South India.